2004
DOI: 10.1021/bi036231a
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Probing of Membrane Transport in Living Microbial Cells Using Single Nanoparticle Optics and Living Cell Imaging

Abstract: Membrane transport plays a leading role in a wide spectrum of cellular and subcellular pathways, including multidrug resistance (MDR), cellular signaling, and cell-cell communication. Pseudomonas aeruginosa is renowned for its intriguing membrane transport mechanisms, such as the interplay of membrane permeability and extrusion machinery, leading to selective accumulation of specific intracellular substances and MDR. Despite extensive studies, the mechanisms of membrane transport in living microbial cells rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
313
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(322 citation statements)
references
References 37 publications
7
313
0
2
Order By: Relevance
“…The toxicity of nAg to bacteria is greatly influenced by nAg particle size and shape. While nAg synthesis and uptake in bacteria has been reported for spheres and rods up to 80 nm (Pal et al, 2007), particles in the range of 1 to 10 nm with high density <111> facets are most likely to interact negatively with the cell (Xu et al, 2004;Morones et al, 2005;Gogoi et al, 2006;Pal et al, 2007).…”
Section: Antibacterial and Antiviral Properties Of Silver Nanoparticlmentioning
confidence: 99%
“…The toxicity of nAg to bacteria is greatly influenced by nAg particle size and shape. While nAg synthesis and uptake in bacteria has been reported for spheres and rods up to 80 nm (Pal et al, 2007), particles in the range of 1 to 10 nm with high density <111> facets are most likely to interact negatively with the cell (Xu et al, 2004;Morones et al, 2005;Gogoi et al, 2006;Pal et al, 2007).…”
Section: Antibacterial and Antiviral Properties Of Silver Nanoparticlmentioning
confidence: 99%
“…G old nanoparticles are proving to be a powerful tool to probe cell function and behaviour 1,2 . The unique properties of gold allow tagging of cellular components, local amplification of the excitation light field or dynamically reporting the positions and chemical compositions of compounds near the probe 3,4 .…”
mentioning
confidence: 99%
“…Sondi et al (2004) observed the accumulation of Ag-NPs in E. coli membrane with subsequent damage to the bacterial membrane. Xu et al (2004) reported that Ag-NPs with size ranging up to 80 nm can accumulate within the bacteria (Ps. aeruginosa) and such accumulation might be related to membrane permeability.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%